(untitled) (Research, Society and Development, 2021)
Objective: To describe the quality of life of people with HIV/hepatitis C coinfection. Method: Systematic review guided by the question "How is the quality of life of people living with HIV//hepatitis C coinfection?" The PECO strategy was used to select descriptors in Portuguese, English, and Spanish, allowing the bibliographic search in April 2021 in the Embase, Scopus, PubMed, CINAHL, Academic Search Premier, SocINDEX, and LILACS databases without limitation of period of publication. Two independent reviewers performed study selection and data extraction. Results: A total of 1,536 publications were identified, of which 14 were included in this review. It was identified that people with HIV//hepatitis C coinfection have several domains with impaired quality of life, which is worse when compared to the general population without morbidities and people with HIV or hepatitis C monoinfection. It was also identified that the treatment for hepatitis C in people with coinfection has a positive impact on quality of life, especially in patients with a sustained virological response and in treatments free of interferon and ribavirin. Conclusion: The study showed that people with HIV/hepatitis C coinfection have impaired quality of life in aspects ranging from physical to social domains. Therefore, the approach to the quality of life of these people shall be implemented in health services to contribute to the redefinition of living with two chronic diseases and to reorient care towards the most affected aspects in these people.